2021
DOI: 10.1002/pits.22582
|View full text |Cite
|
Sign up to set email alerts
|

Educator perspectives on mental health resources and practices in their school

Abstract: The need for mental health services in schools is increasing. Teachers are expected to meet student's academic needs but may find their role impacted by the need for mental health support among students (Bruhn et al., 2014; Kaffenberger & O'Rouke‐Trigiani, 2013). The purpose of this study is to elicit teacher perspectives on addressing the mental health needs of students in school. Staff members from one school in a Midwestern state were interviewed to examine their perspectives related to student mental healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 55 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…Children with low self-esteem will feel inadequate, feel helpless, reduce their sense of self-worth, question themselves, or give up their [14], as shown in Figure 5 below. Therefore, the primary school teachers always maintain an active will quality and let the students experience the full support and respect of the teachers, to create a high degree of selfesteem.…”
Section: Influence On Students' Personality Developmentmentioning
confidence: 99%
“…Children with low self-esteem will feel inadequate, feel helpless, reduce their sense of self-worth, question themselves, or give up their [14], as shown in Figure 5 below. Therefore, the primary school teachers always maintain an active will quality and let the students experience the full support and respect of the teachers, to create a high degree of selfesteem.…”
Section: Influence On Students' Personality Developmentmentioning
confidence: 99%
“…As one participant noted (T2), teachers, especially kindergarten teachers, are often a child’s first contact in school and are therefore responsible for identifying students in need of extra socioemotional support. Since teachers view themselves as the first line of defense in identifying students in need of support and providing universal instruction on socioemotional competencies (Ormiston et al, 2021 ), teachers should have the training to identify students with mental health challenges (Papadopoulou et al, 2014 ) and are encouraged to be a regular presence on multi-disciplinary MTSS teams (Brovokich & Dirsmith, 2021 ). Universal school-based socioemotional programs delivered by classroom teachers foster a common language and improve social and emotional skills, behaviors, and academic achievement (Durlak et al, 2011 ).…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Interviews were conducted by five members of the research team, which included four doctoral graduate students and one school psychology faculty member. We adopted interview questions from Ormiston et al ( 2021 ), found in the ‘ Appendix ’, which addressed student mental health within the primary school, and individual and systemic practices currently in place to support student mental health concerns. As stated previously, all interview data was collated and shared with school administrators and staff via an executive summary, as a mechanism for member checking.…”
Section: Methodsmentioning
confidence: 99%
“…Teachers are in a unique position to observe trauma symptoms and how they manifest in the classroom socially, emotionally, behaviorally, and academically. Indeed, teachers recognize the important role they play in addressing and supporting student mental health (Ormiston et al, 2021;Reinke et al, 2011), but their dearth of knowledge and preparation leads to feeling a lack of efficacy in being able to address students' mental health needs (Ormiston et al, 2021;Reinke et al, 2011;Walter et al, 2006). For instance, one study of teachers in Australia found that while teachers reported having professional development (PD) related to mandatory reporting, they did not know how to respond to individuals with trauma exposure (Berger et al, 2021).…”
Section: Teacher Knowledge Of Traumamentioning
confidence: 99%